DYNAMICS OF MASS PHENOMENA ON THE EXAMPLE OF AN ACTIVE LANDSLIDE - Szafarczyk, Anna (Journal of Applied Engineering Science, 2019)
The process of landslides is often carried out over long periods of time and is conditioned by the action of three groups of factors: an accidental, cyclical and main factor. The separation of the long-term tendency (isolation of the main factor) requires elimination of the seasonal (cyclic) and accidental factor. The article presents the results of geodesic surveys of a selected landslide, which was activated by opencast mining. Geodetic measurements were carried out with a ground based radar interferometer in GBInSAR technology and a GPS receiver in RTN technology. For the obtained data, a method was presented that allows to isolate a cyclic factor in a 24-hour period. The elimination of the cyclical factor allowed to distinguish the long-term tendency and determine the nature of the trend.